Graph of Pythagorean Neutrosophic Fuzzy Ideal at Near Rings of M gamma Groups and its Maximal Product - K.V. Udayanatchi,; O.V. Shanmuga Sundaram, (Utilitas Mathematica, 2025)
Fuzzy sets have shown themselves to be a dependable subject of study in numerous domains. They are an excellent option for the simplification and extension of classical sets due to their simplicity and flexibility. This paper describes the maximal product of two Pythagorean Neutrosophic Fuzzy Ideal Graphs(PNFIG) and maximal product of two Strong Pythagorean Neutrosophic Fuzzy Ideal Graphs(SPNFIG) in the M group of near rings. The degree of a vertex is discussed in detail along with a few theorems for the maximal product of PNFI graph structures. The Pythagorean Neutrosophic Fuzzy Set [PNFS] is a generalization of the Pythagorean Fuzzy Set(PFS) with condition 0≤????(s)2+????(s)2+ ????(s)2≤2 and neutrosophic set with dependent neutrosophic components. Thus we extend some of the basic properties for this PNFIG along with few examples.